Interactive non-photorealistic rendering - Al-Rousan, Riyad (Penerbit UTM Press, 2015)
Due to increasing demands of artistic style with Interactive Rate, we propose this review paper as a starting point for any person interested in researching of interactive non-photorealistic rendering. As a simple yet effective means of visual communication, interactive non-photorealistic rendering generates images that are closer to human-drawn than are created by traditional computer graphics techniques with more expressing meaningful visual information. This paper presents taxonomy of interactive non-photorealistic rendering techniques which developed over the past two decades, structured according to the design characteristics and behavior of each technique. Also, it covers the most important algorithms in interactive stylized shade and line drawing, and separately discussing their advantages and disadvantages. The review then concludes with a discussion of the main issues and technical challenges for Interactive Non-Photorealistic Rendering techniques. In addition, this paper discusses the effect of modified phong shading model in order to create toon shading appearance.